Weight-of-the-evidence evaluation of 2, 4-D potential for interactions with the estrogen, androgen and thyroid pathways and steroidogenesis. (28th May 2017) - Neal, B. H.; Bus, J.; Marty, M. S.; Coady, K.; Williams, A.; Staveley, J.; Lamb, J. C.
Abstract: A comprehensive weight-of-the-evidence evaluation of 2, 4-dichlorophenoxyacetic acid (2, 4-D) was conducted for potential interactions with the estrogen, androgen and thyroid pathways and with steroidogenesis. This assessment was based on an extensive database of high quality in vitro, in vivo ecotoxicological and in vivo mammalian toxicological studies. Epidemiological studies were also considered. Toxicokinetic data provided the basis for determining rational cutoffs above which exposures were considered irrelevant to humans based on exceeding thresholds for saturation of renal clearance (TSRC); extensive human exposure and biomonitoring data support that these boundaries far exceed human exposures and provide ample margins of exposure. 2, 4-D showed no evidence of interacting with the estrogen or androgen pathways. 2, 4-D interacts with the thyroid axis in rats through displacement of thyroxine from plasma binding sites only at high doses exceeding the TSRC in mammals. 2, 4-D effects on steroidogenesis parameters are likely related to high-dose specific systemic toxicity at doses exceeding the TSRC and are not likely to be endocrine mediated. No studies, including high quality studies in the published literature, predict significant endocrine-related toxicity or functional decrements in any species at environmentally relevant concentrations, or, in mammals, at doses below the TSRC that are relevant for human hazard and risk assessment. Overall, there is no basis for concern regarding potential interactions of 2, 4-D with endocrine pathways or axes (estrogen, androgen, steroidogenesis or thyroid), and thus 2, 4-D is unlikely to pose a threat from endocrine disruption to wildlife or humans under conditions of real-world exposures.